2014
DOI: 10.7150/ijms.8331
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone vs. Fentanyl Patient-Controlled Analgesia after Laparoscopic Cholecystectomy

Abstract: Objectives Oxycodone is semi-synthetic opioid, oral and parenteral preparations have been widely used for acute and chronic pain. The aim of this study was to assess the efficacy and side effects of oxycodone and fentanyl in patient controlled analgesia (PCA) after laparoscopic cholecystectomy.Methods A prospective, randomized, double-blind study was conducted. 81 patients were randomly divided into two groups; fentanyl (10 mcg fentanyl and 1.5 mg ketorolac) and oxycodone group (1 mg oxycodone and 1.5 mg ketor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(117 citation statements)
references
References 18 publications
5
106
4
Order By: Relevance
“…In a subsequent study in patients scheduled for laparoscopic cholecystectomy, IV-PCA oxycodone provided comparable effects for pain relief compared to IV-PCA fentanyl in a potency ratio of 1:75. [19] In a study of 60 laparoscopic hysterectomy, patients were randomized to receive PCA oxycodone or PCA fentanyl (potency ratio 100:1) following surgery find that oxycodone presented a better analgesic effect, also resulted in a higher occurrence of postoperative nausea and vomiting. [20] In another recent similar study, the potency ratio was 60:1, and both agents were found to provide similar analgesic efficacy and similar rates of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study in patients scheduled for laparoscopic cholecystectomy, IV-PCA oxycodone provided comparable effects for pain relief compared to IV-PCA fentanyl in a potency ratio of 1:75. [19] In a study of 60 laparoscopic hysterectomy, patients were randomized to receive PCA oxycodone or PCA fentanyl (potency ratio 100:1) following surgery find that oxycodone presented a better analgesic effect, also resulted in a higher occurrence of postoperative nausea and vomiting. [20] In another recent similar study, the potency ratio was 60:1, and both agents were found to provide similar analgesic efficacy and similar rates of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The pain score was evaluated with an 11-point numerical rating scale (0=no pain, 10=the worst imaginable pain). Patients were asked to rank their satisfaction with postoperative pain management at 24 and 48 hours after the initial thoracic paravertebral levobupivacaine injection according to the following scale: 1=very unsatisfactory, 2=unsatisfactory, 3=neutral, 4=satisfactory, and 5=very satisfactory 14. The records of postoperative fentanyl consumption were extracted from the internal memory of the CADD-Solis Ambulatory Infusion Pump and managed with the CADD-Solis Medication Safety Software (Smiths Medical).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is significant debate regarding the equipotent ratio of fentanyl to oxycodone. Hwang et al [19] reported that the potency ratio was 1:75 in laparoscopic cholecystectomy, and oxycodone showed comparable effects for pain relief compared to fentnayl in spite of a smaller cumulative PCA dose. In other recent studies, the potency ratio of fentanyl and oxycodone was found to be 1:62.5 in gastrointestinal laparotomy, 1:60 in laparoscopic benign gynecological surgery, and 1:55 in colorectal surgery, and oxycodone was shown to provide similar analgesic efficacy to that of fentanyl [20][21][22].…”
mentioning
confidence: 99%
“…Oxycodone is an effective analgesic agent for visceral pain and somatic pain, but studies to date have shown that it is more effective for visceral pain [7][8][9]27]. Likewise, pain after abdominal surgery is controlled by similar or smaller amounts of oxycodone compared with the equipotent ratio of morphine or fentanyl [16][17][18][19][20][21][22]. Therefore, in somatic pain such as pain after orthopedic surgery, the amount of oxycodone should be higher than the dose used for visceral pain.…”
mentioning
confidence: 99%